Theorising sexual harassment and criminalisation in a Swedish context - Wegerstad, Linnea (Bergen Journal of Criminal Law & Criminal Justice, 2022)
This article offers a theoretical approach to criminalisation in relation to sexual harassment, using Sweden as example. The topic is spurred by two separate but interrelated phenomena. The first is the #metoo movement, which raised not only awareness of the widespread problem of sexual harassment, but also questions as to whether criminal law can provide a proper response. The second is a growing concern, both in international research and among Swedish activists, that the feminist struggle against sexual violence is turning towards punitive measures. Taking the standpoint that feminist research and activism should engage in a critical conversation with criminal law and crime policy, this article employs Kelly’s concept of the continuum of sexual violence to analyse the scope for criminal law interventions regarding men’s intimate intrusions against women. Swedish criminal regulation is used to highlight some of the challenges of designing a criminal provision that considers the individual effects as well as the cumulative and collective impacts of sexual harassment.